Abnormalities of Brain White Matter in Type 2 Diabetes Mellitus: A Meta-Analysis of Diffusion Tensor Imaging - Huang, Li; Zhang, Qingqing; Tang, Tong; Yang, Minguang; Chen, Cong; Tao, Jing; Liang, Shengxiang (Frontiers in Aging Neuroscience, 2021)
Aims: The study aimed to conduct a meta-analysis to determine the abnormalities of white matter in patients with type 2 diabetes mellitus (T2DM) by identifying the consistency of diffusion tensor imaging (DTI). Method: The literatures for diffusion tensor imaging comparing T2DM patients with controls which published before October 30, 2020 were reviewed in PubMed, Web of Science, Embase, CNKI and Wan Fang database. The meta-analysis was performed using the activation likelihood estimation method, including 12 reports and 381patients with T2DM. Results: The meta-analysis identified 10 white matter regions that showed consistent reduction of FA in patients with T2DM, including genu of corpus callosum, body of corpus callosum, bilateral anterior corona radiata, bilateral superior corona radiata, bilateral cingulum and bilateral superior fronto-occipital fasciculus. Conclusion: This study revealed the abnormal characteristic of white matter in T2DM, which would be helpful to understand the underlying neuropathological and physiological mechanisms of T2DM, and provide evidence for clinical diagnosis and treatment.